Performance Evaluation of the OraQuick Hepatitis C Virus Rapid Antibody Test - Cha, Young Joo; Park, Quehn; Kang, Eun-Suk; Yoo, Byung Chul; Park, Kyoung Un; Kim, Jin-Wook; Hwang, Yoo-Sung; Kim, Myung Hee (Annals of laboratory medicine, 2013)
A reliable rapid assay for hepatitis C virus (HCV) may be helpful in various clinical settings. We evaluated the performance of the OraQuick HCV Rapid Antibody Test (OraSure Technologies Inc., Bethlehem, PA, USA). Clinical sensitivity and specificity were evaluated with oral fluids and sera from 137 patients diagnosed with hepatitis C and 300 healthy blood donors in a multi-center collaborative study. The stored sera of 200 proven HCV-infected patients and 200 healthy subjects were also evaluated. Analytical sensitivity was estimated with 4 commercial seroconversion panels and 7 Korean reference panels. The performance of 4 laboratory-based tests (3 chemiluminescence assays and 1 enzyme immunoassay) and 4 rapid test kits was compared. We also assessed the interference due to bilirubin, hemoglobin, lipid, rheumatoid factor, multipara, and several viral infections. The clinical sensitivity and specificity of the OraQuick HCV test using oral fluid were 97.8% (95% confidence interval [CI], 93.2-99.4%) and 100% (95% CI, 98.4-100%), respectively. The clinical sensitivity using serum samples was 100%. Using the 4 seroconversion panels, the OraQuick HCV test showed results comparable to those of the laboratory-based assays; its analytical sensitivity was higher than that of the other rapid test kits. There was no cross-reactivity with common interfering factors. The clinical performance of the OraQuick HCV Test is comparable to that of laboratory-based tests with both serum and oral fluid. This supports the supplementary use of rapid HCV testing using oral fluid in various medical and non-medical settings.